2000
DOI: 10.1210/jc.85.6.2170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine on Muscle Glycogen Utilization and the Neuroendocrine Axis during Exercise

Abstract: To examine the effect of caffeine ingestion on muscle glycogen utilization and the neuroendocrine axis during exercise, we studied 20 muscle glycogen-loaded subjects who were given placebo or caffeine (6 mg/kg) in a double blinded fashion 90 min before cycling for 2 h at 65% of their maximal oxygen consumption. Exercise-induced glycogen depletion in the thigh muscle was noninvasively measured by means of 13C nuclear magnetic resonance spectroscopy (NMR) spectroscopy, and plasma concentrations of substrates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 0 publications
6
71
1
4
Order By: Relevance
“…1 shows declining cortisol levels on the placebo day from the preexercise (C+60) time period through 40 min postexercise (Post+40). Exercise that is of short duration and moderate intensity may not activate a cortisol response if glucose levels remain normal (Sung et al, 1990), although long duration and intense exercise will increase cortisol output to high levels as a function of metabolic demands on fuel homeostasis (Laurent et al, 2000;Luger et al, 1987;Scavo et al, 1991). Despite the moderate intensity of the exercise protocol we used, the much larger HPA response to the mental stressors is striking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 shows declining cortisol levels on the placebo day from the preexercise (C+60) time period through 40 min postexercise (Post+40). Exercise that is of short duration and moderate intensity may not activate a cortisol response if glucose levels remain normal (Sung et al, 1990), although long duration and intense exercise will increase cortisol output to high levels as a function of metabolic demands on fuel homeostasis (Laurent et al, 2000;Luger et al, 1987;Scavo et al, 1991). Despite the moderate intensity of the exercise protocol we used, the much larger HPA response to the mental stressors is striking.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine increases cortisol levels during periods of stress (Lovallo et al, 1989(Lovallo et al, , 1996Lane et al, 1990;Sung et al, 1990) both in the lab and in daily life (Lane, 1994), during naturalistic stressors such as medical school examinations (Shepard et al, 2000), and in relation to exercise (Laurent et al, 2000;Sung et al, 1990). Caffeine's effect on cortisol may be greater in persons with higher levels of central nervous system activation, such as those at high risk for hypertension (al'Absi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que as concentrações de IgA-s são reduzidas tanto durante (gleeson et al, 1999) quanto após (nieMan et al, 2002) períodos de exercício extenuantes tanto pela intensidade como pela duração. Essa redução parece estar associada ao aumento nos níveis de cortisol, que também é elevado em exercícios agudos vigorosos seguidos da ingestão de cafeína (huCkleBridge, CloW;evans, 1998;laurent et al, 2000). Lovallo et al (2006) afirmam que a cafeína eleva a secreção de cortisol, assim como o exercício, e ressalta que, quando combinamos os dois fatores, há um efeito substancial e prolongado em homens.…”
Section: Resultsunclassified
“…However, researchers who studied the effect of caffeine intake on the use of MG during aerobic exercise found no differences between caffeine intake and the placebo (Laurent, Schneider, Prusaczyk, Franklin, Vogel et al, 2000). Other authors also observed that post-exercise caffeine intake results in an increase in the rate of resynthesis of muscle glycogen in the recovery period after strenuous exercise (Pedersen, Lessard, Coffey, Churchley, Wootton, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%